Rice land sustainability and agricultural financing through waqf - Rifaldi Majid (Center for Islamic Economics and Development Studies [P3EI], 2022)
Purpose – This paper aims to formulate a waqf of rice field model combined with the mitigating risk associated with maintaining the agricultural land due to the conversion issue.Methodology – This study used a qualitative method with a library approach by adopting a qualitative content analysis which strengthens primary data collection through in-depth interviews with experts consisting of regulators, practitioners, and academics in the fields of waqf and agricultureFindings – The results showed that the strategy to implement the waqf of rice fields could be pursued by an internal strategy, namely optimizing and revitalizing waqf land. That had been pledged as a means of production and an external strategy through the acquisition of potential paddy fields for waqf and managed by nazhir. In implementing the proposed model, some institutional engineering is needed, namely by presenting the role of anchor companies as managers, farmer associations of driving actors, and off-takers who buy crops. It can mitigate the risk of reduced cash waqf principal and farmer financing through a holistic feasibility study, involvement of insurance/guarantor, reserving capital funds, restructured financing, blended finance schemes, and institutional strengthening.Implications – This model expects to answer the sustainability problem of agricultural land, be a catalyst for increasing production quantity, and solve the financing issue for farmers.Originality – This preliminary study integrated the agricultural issues with the concept of waqf and Islamic instruments strengthened by literature review and expert judgment, followed by formulating the proposed model's strategies, models, and risk mitigation.